Amerikan Hekimler Birliği (AMA) Kalıcı Özürlülüğün Değerlendirmesi Kılavuzu - Bilgin, Nursel Gamsız (The Bulletin of Legal Medicine, 2019)
A single guide which is prepared according to the scientific criteria and will allow the calculation in a way that does not leave any discretion has become necessary for our country. This review has been prepared to provide information about the Disability Assessment Manual used by the American Medical Academy, which we think will eliminate the current problems in our country.